Upaya Meningkatkan Pemahaman Siswa pada Pelajaran Agama Islam Materi Mengenal Kitab Allah melalui Metode Make A Match Siswa Kelas V SDN 21 Pilubang - Ali Imran; Putri Ayu; Zomiliarif Zomiliarif; Dewi Kurnia (Kampus Akademik Publiser, 2024)
This study was motivated by the low level of understanding among fifth-grade students at SDN 21 Pilubang regarding the material on learning about the books of Allah in Islamic Religious Education. The pre-cycle results showed that only 11% of students achieved learning completeness with a score of ≥80, while the majority of students were still below the Minimum Completeness Criteria (KKM). This condition was influenced by the use of a lecture method that lacked variety, causing students to become passive, bored, and unenthusiastic in learning. To overcome this problem, this study applied the Make a Match method as a cooperative learning strategy that emphasized student activity in finding pairs of question and answer cards interactively. This study is a Classroom Action Research (CAR) conducted in two cycles, with 15 fifth-grade students as research subjects. Data were collected through tests, observations, and documentation, then analyzed descriptively, quantitatively, and qualitatively. The results showed a significant increase in student understanding. In cycle I, learning completeness increased in terms of activity, although the achievement rate was still only 11%. However, in cycle II, the percentage of learning completeness rose to 38%, with teacher and student activity reaching 100%. Thus, the Make a Match method proved to be effective in improving students' understanding in learning about the books of Allah.